Emergency Response with Potato and Sweetpotato among drought-affected farmers in SNNPR, Ethiopia - International Potato Center (2017)
The Emergency potato and sweetpotato seed support enabled farmers in the Southern Nations Nationalities and People’s Region (SNNPR) to restore the varieties they lost to a severe drought in 2015/2016, improving their household food and nutrition security. In one year, 9,779 farmers got sweetpotato. cuttings and 23,594 were trained on sweetpotato agronomy and nutrition